Thermoanalytical study of purine derivatives compounds - Schnitzler, Egon; Kobelnik, Marcelo; Sotelo, Gabriel Federico Calle; Bannach, Gilbert; Ionashiro, Massao (Eclética Química, 2004)
Thermal methods of analysis are now used in a very large range of scientific investigations. In this work simultaneous thermogravimetry-differential thermal analysis (TG-DTA), X-Ray powder diffractometry and infrared spectroscopy were used to study the derivative compounds of purine, i. e. aminophylline, theophylline, caffeine and uric acid. The results led to informations about the thermal stability and thermal decomposition of these compounds.